Laboratory Investigation of Soil Suffusion Through Particle Size Distribution and Hydraulic Conductivity Analysis - Imtiyaz Akbar, Najar; Raudhah, Ahmadi; Raghad, Mourad; Neveen El, Bendary; Shanshan, Tang; Azrin, Ahmad; Yunika Kirana, Abdul Khalik; Mohd Nur-Faiz, Haris (Springer Nature Link, 2025)
Internal erosion, particularly suffusion, poses a critical risk to soil stability and infrastructure resilience in regions with continuous heavy rainfall. Despite extensive research, existing models fail to accurately predict suffusion progression in heterogeneous and soft soils under fluctuating hydraulic conditions. Four distinct soil types were studied: very soft clayey silt, soft clayey silt, hard clayey silt, and stiff clay. This study addresses these gaps by investigating the effects of suffusion on particle size distribution, void ratio, and hydraulic conductivity in soils near the Lubok Antu Bridge in Malaysia. Controlled hydraulic gradient experiments revealed that hydraulic conductivity increases significantly with loss of fines, particularly in soils with lower clay content. The particle size distribution analysis demonstrated a downward shift in the particle size distribution curves, confirming substantial erosion of fines. Changes in the void ratio were linked to both loss of fines and volumetric deformation, with soils exhibiting either dilative or contractive behaviour based on their initial void ratio. The study further evaluated empirical models, identifying limitations in their predictive accuracy for complex soil structures. Findings emphasize the importance of integrating hydraulic properties and fines content into the design and maintenance of infrastructure in hydrologically active regions.